Clustering of Leading Food Products in the south Sumatra Region (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to identify and cluster regional superior food products in the South Sumatra region based on the agricultural, plantation and fisheries sectors using the Location Quotient (LQ) method and a descriptive quantitative approach. South Sumatra agricultural, plantation and fisheries production data starting from 2020-2022 is compared to total production in Indonesia to assess the LQ of each commodity. Policy recommendations include: developing location-specific agricultural infrastructure and technology, increasing added value and standardizing quality, as well as promoting cluster-based products to increase the competitiveness of South Sumatra’s superior food products. The research results show 3 main clusters, namely rice (agriculture) producing a total production of 2.7 million tons, production based in Banyuasin Regency, oil palm (plantation) producing a total production of 2.4 million tons, production based in Musi Banyuasin Regency, fisheries which resulted in total production reaching 236 thousand tons of production based in Musi Rawas Regency.